2016
DOI: 10.1155/2016/3016149
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of New Aspergillus Strains for Proteolytic Enzymes Production by Solid State Fermentation

Abstract: A comparative study of the proteolytic enzymes production using twelve Aspergillus strains previously unused for this purpose was performed by solid state fermentation. A semiquantitative and quantitative evaluation of proteolytic activity were carried out using crude enzymatic extracts obtained from the fermentation cultures, finding seven strains with high and intermediate level of protease activity. Biochemical, thermodynamics, and kinetics features such as optimum pH and temperature values, thermal stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 42 publications
1
15
0
3
Order By: Relevance
“…The values of V max , K m , K cat , and K cat /K m measured for the partially purified protease were summarized in Table 1. The K m value of an enzyme indicates the affinity of the enzyme for its substrate: a low value of this parameter indicates a higher affinity [36]. It was observed that purified protease of S. marcescens had high affinity for its substrate compare to the purified protease of P. putida with K m value 0.3 and 0.5 mg/ml, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of V max , K m , K cat , and K cat /K m measured for the partially purified protease were summarized in Table 1. The K m value of an enzyme indicates the affinity of the enzyme for its substrate: a low value of this parameter indicates a higher affinity [36]. It was observed that purified protease of S. marcescens had high affinity for its substrate compare to the purified protease of P. putida with K m value 0.3 and 0.5 mg/ml, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The activation energy (E a ) of protease was determined by using azocasein as a substrate at several temperatures ranging from 20 to 40 °C. The E a was calculated from the slope of linear Arrhenius plot (1) of ln [Protease Activity] versus 1/T, where E a = −slope × R, R (gas constant) = 8.314 J/K/mole, and T is the absolute temperature in Kelvin (K) [36], [44].ln(protease activity)=()-EaR×1T+lnA…”
Section: Methodsmentioning
confidence: 99%
“…Plaklar 37°C'de 24 saat bekletilmiş, koloni etrafındaki şeffaf zon varlığı kazeinaz aktivitesi olarak değerlendirilmiştir (8) . Fosfolipaz üretimi yumurta sarılı Sabouraud Dekstroz Agar (SDA, Difco) besiyerinde (13.0 g; NaCl (Sigma), 11.7 g; CaCl 2 (Sigma), 0.11 g; and %10 steril egg yolk emülsüyonu (Sigma), 184 mL of distile su) incelenmiştir.…”
Section: İn Vitro Virülans çAlışmalarıunclassified
“…Her kökenden serum fizyolojik (SF) içinde hazırlanan süspansiyon 5x10 8 hücre içerecek şekilde sulandırılmıştır. Süspansiyondan 10 µl Hamilton enjektörü içine alınmıştır.…”
Section: İn Vitro Virülans çAlışmalarıunclassified
“…A. oryzae mainly secretes neutral protease, with relatively low alkaline protease and acid protease activities, thus, presenting low degradation and utilization of raw protein (Zhao et al, 2014). To meet the needs of the fermentation industry, researchers are committed to develop new A. oryzae strains with high protease activity to improve raw protein utilization and composition of fermentation products (Ortiz et al, 2016;Xu et al, 2011;Fang et al, 2009). Genetic engineering has been reported to significantly enhance the protease activity of A. oryzae (te Biesebeke et al, 2005;Hunter et al, 2013;Olempska-Beer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%